2019
DOI: 10.3389/fevo.2019.00042
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Predator Nutrient Intake From Prey Body Contents

Abstract: Predator-prey interactions can have important consequences for the flow of nutrients through food webs and ecosystems. Given the diversity of predator-prey interactions, it is infeasible to directly measure predator nutrient intake when feeding on each potential prey. Elements are an important measure of nutrient flow through food webs but do not fully account for variation in the quality of nutrients in which they are present. The overall goal of this study was to test if measures of macronutrients, metaboliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Yet, the few studies explicitly investigated this relationship and also found no or weak links (Wilder & Jeyasingh, ; Zhang, Jansen, Smolders, De Meester, & Stoks, ). To advance insights into the (de)coupling between elemental and macromolecular body contents, it may be important to study in more detail the macromolecular content of the exoskeleton (Wilder, Barnes, & Hawlena, ) as this makes up an important part of the total body mass in insects (Lease & Wolf, ). Furthermore, better characterizing the macromolecules may be important.…”
Section: Conclusion and Ways Forwardmentioning
confidence: 99%
“…Yet, the few studies explicitly investigated this relationship and also found no or weak links (Wilder & Jeyasingh, ; Zhang, Jansen, Smolders, De Meester, & Stoks, ). To advance insights into the (de)coupling between elemental and macromolecular body contents, it may be important to study in more detail the macromolecular content of the exoskeleton (Wilder, Barnes, & Hawlena, ) as this makes up an important part of the total body mass in insects (Lease & Wolf, ). Furthermore, better characterizing the macromolecules may be important.…”
Section: Conclusion and Ways Forwardmentioning
confidence: 99%
“…Energetic and elemental analysis alone can be a poor predictor of energy available in prey (Wilder et al 2019). Elemental analyses of prey items can identify coarse measures of quality but are unable to distinguish between compounds that have similar elemental content but different digestibility (Anderson and Pond 2000;Anderson et al 2004;Wilder and Eubanks 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies to date have considered the ecological stoichiometry and elemental nutrition of spiders (e.g., [32,35,[40][41][42]); therefore, a large gap in data exists, and it is hard to perform comparisons leading to strong and meaningful conclusions. Hence, we will supplement our reasoning with available data collected for other arthropods.…”
Section: Discussionmentioning
confidence: 99%
“…Processes involved in ecophysiology and life history evolution are likely to differentially affect females and males, imposing sex-specific nutritional limitations and even imposing a conflict between the sexes in reaching sex-specific nutritional optima [13,23]. At the same time, stoichiometric phenotypes are species-specific and reflect the nutritional demands of individuals [15,24,32]. Therefore, we hypothesized (1) that taxon-specific and sex-specific differences in the multielemental stoichiometry of the studied spiders and in their stoichiometric niches would be observed.…”
Section: Hypothesesmentioning
confidence: 99%